Gafchromic XR‐QA2 film as a complementary dosimeter for hand‐monitoring in CTF‐guided biopsies - Sarmento, Sandra; Pereira, Joana; Sousa, Maria José; Cunha, Luís; Dias, Anabela G.; Pereira, Miguel F.; Oliveira, Augusto D.; Cardoso, João V.; Santos, Luís M.; Gouvêa, Margarida; Lencart, Joana; Alves, João G.; et al. (Journal of applied clinical medical physics, 2016)
Computed tomography fluoroscopy (CTF) is a useful imaging technique to guide biopsies, particularly lung biopsies, but it also has the potential for very high hand exposures, despite use of quick‐check method and needle holders whenever feasible. Therefore, reliable monitoring is crucial to ensure the safe use of CTF. This is a challenge, because ring dosimeters monitor exposure only at the base of one finger, while the fingertips may be exposed to the highly collimated CT beam. In this work we have explored the possibility of using Gafchromic XR‐QA2 self‐developing film as a complementary dosimeter to quantify hand exposure during CTF‐guided biopsies. A glove used in a previous study and designed to contain 11 TLDs was adapted to include Gafchromic strips 7 mm wide, covering the fingers. A total of 22 biopsies were successfully performed wearing this GafTLD glove under sterile gloves, and the IR reported no difficulty or reduction of dexterity while wearing it. Comparison of dose distributions obtained from digitization of the Gafchromic film strips and absolute Hp(0.07) readings from TLDs showed good agreement, despite some positional uncertainty due to relative movement. Per procedure, doses at the base of the ring finger can be as low as 3%–8% of hand dose maximum. Accumulated dose at the base of the ring finger was four times lower than the dose maximum. PACS numbers: 07.57.Kp, 29.40.‐n, 85.25.Pb, 87.57.qp